The Great triumvirate : Webster, Clay, and Calhoun - Peterson, Merrill D. (Oxford University Press, 1987)
This is a joint biography of Daniel Webster, Henry Clay and John C. Calhoun, the most prominent of the second generation of American statesmen, from 1812 until 1850.